Association between germ-line HLA and immune-related adverse events - Jiang, Ning; Yu, Yue; Zhang, Min; Tang, Yu; Wu, Dawei; Wang, Shuhang; Fang, Yuan; Zhang, Yu; Meng, Lin; Li, Yingying; Miao, Huilei; Ma, Peiwen; et al. (Frontiers in Immunology, 2022)
Background: In recent years, significant progress has been made in immune checkpoint inhibitors (ICIs). However, accompanied by remarkable efficacy, a growing number of immune-related adverse events (irAEs) also arose. The mechanism of irAEs remains unclear. Previous studies indicated a positive association between specific human leukocyte antigen (HLA) variants and irAEs. Therefore, we planned and initiated a large cohort study aiming to uncover the relationship between irAEs and divergent HLA types. Methods: We screened all patients who have been treated in the clinical research ward, Cancer Hospital of the Chinese Academy of Medical Sciences. All participants were diagnosed with malignant tumors with complete AE follow-up data in the original electronic medical records. Sequencing libraries were generated using a customized panel, and four-digit formatted HLA alleles were extracted for further analysis. Association analysis was performed between HLA variants and different irAEs. We introduced two external reference groups and a non-irAE control group within the study cohort to control the type I error. We also explored the relationship between the zygosity of HLA genes, the evolutionary divergence of HLA class I genotype (HED), and irAEs. Results: 530 participants received at least two doses of ICIs. The median follow-up time was 10.3 months. 97% of patients received anti-PD-1/PD-L1 treatment. The occurrence of overall irAEs showed no significant difference between the HLA homozygous group and the HLA heterozygous group. We did not find any significant association between irAEs and HED. We found that some HLA types are associated with irAEs of different organs and detected a significant association between HLA-DRB3*01:01 and thrombocytopenia (OR 3.48 (1.19,9.42), p = 0.011), HLA-DPB1*04:02 and hypokalemia/ hyponatremia (OR 3.44 (1.24,9.1), p = 0.009), leukopenia (OR 2.1 (0.92,4.8) , p = 0.037), anemia (OR 2.33 (1.0,5.41) , p = 0.026), HLA-A*26:01 and bilirubin elevation (OR 2.67 (0.92,8.31) , p = 0.037). Conclusions: IrAEs in specific organs and tissues may be associated with certain HLA types, while HLA heterogeneity has no significant influence on the happening of irAEs. More research is needed to explore the role of germline genetic changes in the risk assessment of irAEs.